1979
DOI: 10.3109/02844317909013069
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Articular Cartilage with Free Autologous Perichondrial Grafts

Abstract: An experimental study in adult rabbits has been performed to find out whether the cartilage forming capacity of the perichondrium could be utilized in reconstruction of articular cartilage. The normal articular cartilage of the glenoid surface of the humero-scapular joint was completely removed. Auricular perichondrium was grafted to cover the exposed bony surface with the active chondrogenic layer of the perichondrial graft facing the joint cavity. The joint was not immobilized but the operated limb was amput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 12 publications
0
25
0
2
Order By: Relevance
“…Spontaneous healing is poor, and shaving and drilling the lesions result in fibrocartilage which is mechanically inferior to articular cartilage. Rib perichondrium has the potential to differentiate into cartilage with similar properties to hyaline cartilage [2,3,6,10]. Our study shows that the success of this procedure depends on the selection of patients.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Spontaneous healing is poor, and shaving and drilling the lesions result in fibrocartilage which is mechanically inferior to articular cartilage. Rib perichondrium has the potential to differentiate into cartilage with similar properties to hyaline cartilage [2,3,6,10]. Our study shows that the success of this procedure depends on the selection of patients.…”
Section: Discussionmentioning
confidence: 82%
“…From September 1986 to December 1992, 88 patients with articular cartilage defects were treated by perichondrial arthroplasty in the University Hospital, Maastricht [2,8,16,25,26]. The study was approved by the local ethics committee and was performed in accordance with the ethical standards laid down by the 1994 Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1972 Skoog et al showed the chondrogenic capacity of free perichondrial grafts. Free perichondrial grafts were used in experimental reconstruction of articular cartilage defects by Ritsila & Alhopuro (1975) and Engkvist (1979).…”
Section: Discussionmentioning
confidence: 99%
“…Periosteal or perichondrial grafts have been used for treatment of localised cartilage defects in animals. However, the results of transplantation with both periosteum and perichondrium are inconsistent [8,23,24]. Thus, a variety of strategies has been employed for managing articular cartilage defects of the knee.…”
Section: Introductionmentioning
confidence: 99%